2009
DOI: 10.1007/s13277-009-0009-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of Crk/Dock180/Rac1 pathway in the malignant behavior of human ovarian cancer cell SKOV3

Abstract: Small GTPases, particularly the Rho family, are key regulators of cell motility and migration. Dock180 was well known for the main target of signal adaptor protein Crk and acted as a guanine-nucleotide exchange factor for small GTPase Rac1. In the present study, Dock180 was found to combine primarily with CrkI other than CrkII, and its association with Elmo1 was also demonstrated in ovarian cancer cell SKOV3. To evaluate the role of Dock180 in human ovarian cancer cell, we performed RNAi-mediated knockdown of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 33 publications
(39 reference statements)
0
33
0
Order By: Relevance
“…Since cells overexpressing PTPN4 grow more slowly and reach confluence at a lower density [8], and PTPN4's interacting partner CrkI functions in intracellular signaling related to cell motility and proliferation [29], we reasoned that PTPN4 may inhibit cell growth and mobility through CrkI. Consistent with this idea, the cell proliferation assay revealed that co-expression of PTPN4 and CrkI significantly inhibited HeLa cell growth compared with that of controls transfected with CrkI alone (Fig.…”
Section: Ptpn4 Inhibits Crki-mediated Cell Growth and Mobilitymentioning
confidence: 67%
See 2 more Smart Citations
“…Since cells overexpressing PTPN4 grow more slowly and reach confluence at a lower density [8], and PTPN4's interacting partner CrkI functions in intracellular signaling related to cell motility and proliferation [29], we reasoned that PTPN4 may inhibit cell growth and mobility through CrkI. Consistent with this idea, the cell proliferation assay revealed that co-expression of PTPN4 and CrkI significantly inhibited HeLa cell growth compared with that of controls transfected with CrkI alone (Fig.…”
Section: Ptpn4 Inhibits Crki-mediated Cell Growth and Mobilitymentioning
confidence: 67%
“…In this way, CrkI functions as a signaling adaptor protein to mediate diverse cellular responses, including proliferation, differentiation and migration [25][26][27]. Overexpression of CrkI has been detected in many types of human cancer cells [16,[28][29][30][31]. A possible role has been suggested for CrkI during these tumorigenesis events, specifically in mediating intracellular signaling related to cell motility and proliferation [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have found that DOCK1 is important in tumor cell function, including cell migration and invasion (Wang et al, 2010), this is the first demonstration of the relationship of DOCK1 with cell migration and gefitinib treatment function in NSCLC A549 cells and establishes DOCK1 as a key target for the effects of enoxaparin and gefitinib in the treatment of NSCLC A549. Interestingly, this downregulation of DOCK1 expression by enoxaparin 1 gefitinib is consistent with the downregulation of pAkt expression.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibmentioning
confidence: 73%
“…RAC1 is a GTPase that belongs to the RAS superfamily of small GTP-binding proteins. Wang et al (2010) implicated Crk/Dock180/ Rac1 in actin cytoskeleton reorganization and thus in cell proliferation, motility, and invasion of the human ovarian cancer cell line SKOV3. EPHA5 is also implicated in the growth, migration, and invasion of cancer cells in culture as well as tumor growth, invasiveness, angiogenesis, and metastasis in vivo (Surawska et al, 2004;Pasquale, 2010).…”
Section: Discussionmentioning
confidence: 99%